Determinación de la Prevalencia de “ehrlichia canis” en la Clínica Veterinaria “Zoosalud” de la Ciudad de La Maná. - Rivadeneira Aguirre, Marcelo Vladimir (2020)
Canine ehrlichiosis is a disease caused by the bacterium Ehrlichia canis, this in turn is a gram negative coconut bacterium which directly infects the circulate cells, this disease directly affects dogs (Eanis familiaris) since its main vector is the brown tick or Rhipicephalus sanguineus. The objective of this research work was to determine the prevalence of this disease in patients who attend the Veterinary Clinic "Zoosalud", which is located in La Maná canton, Cotopaxi province. Hundred animals taken at random were used which came to consultation, regardless of sex, race, age or symptoms presented, what was tried to arrive with this is to find out how many animals had the disease even without still presenting symptoms. A blood sample of 1 to 2 cc was taken directly from the cephalic vein or in certain cases from the saphenous vein, after this it was placed in a tube with EDTA to prevent clotting, placing a drop of blood and two of the Buffer substance that came within the same test. It was waited 10 to 20 min per test and after this; it was marked as negative if there was no trace below the T mark. As results, it was found that there is a percentage of 68% of the presence of Ehrlichia canis, in the clinic mentioned above, taking into account the variables measured, it was found that in males the percentage of positives was 55.9% in males while 44.1 % was found in females. The age variable showed greater susceptibility in canines older than 2 years with a percentage of 48.8%, followed by canines from 9 months to two years with a percentage of 30.7%. These results will allow preventive measures for pet owners.